Sewerage system construction, maintenance and effectiveness of vacuum sewerage system at water village / Harnizah Lamudin - Lamudin, Harnizah (Faculty of Architecture, Planning and Surveying, 2008)
Our planet earth is very different from all the rest of the planets in the sense that almost 3/4 of the earth’s surface are covered by water, which is in turn sustains life. In development also, it must have construction of buildings. Buildings should have maintenance to conserve, control and maintain building from any damage or defect problem. Services also are important systems in building such as electrical, water supply, sewerage system and drainage system. Sewerage is that water carried waste which derives principally from dwellings, businesses, institutions, industry and the like exclusive of any storm, surface and/or ground water. Sewer pipe or conduit for carrying sewage. Sewer system all facilities for collecting, pumping, treating, and disposing of sewage. Sewerage system is one of system to avoid pollution at river. Vacuum Sewerage System is one from types of sewerage system in Malaysia. Vacuum Sewerage System negative pressure system of wastewater transport utilizing differential air pressure to create flow, as opposed to gravity-induced flow of conventional wastewater collection systems.